An Assessment of Institutional Capacity for Social Sector Reform in Argentina - World Bank (Washington, DC, 2013)
The study explores the interactive clash resulting from reforms, and institutional capacity at the provincial level, as the main element to explain current limitations, and to suggest recommendations conducive to further social reform. To understand the framework for past reforms, the study reviews the economic, political, and institutional context within which such reforms were implemented, and examines the national government's reform policy - within the implementation strategy - and, as well, the provincial governments' capacity to manage change - i.e., in three provinces, Catamarca, Cordoba and Salta. The study focuses mainly on education, and health reforms, significantly different in both design, and formulation: health reform only introduced administrative hospital autonomy, merely a partial aspect of a broad health system reform; whereas, the education reform consisted of a total educational system change. The result was that the health reform was supported basically by interested syndicates, who envisaged compensatory benefits, whereas, the actual beneficiaries - the patients - were poorly informed. Conversely, educational reforms were limited by weak capacity at the provincial level, and as well, limited information. An improved educational reform implementation design is recommended, based on institutional capacity building to improve the quality of education, and, suggests a broader health reform within a strategic framework based on public awareness, but which includes the ministries, medical profession, and provincial health workers.